THE FEATURES OF THE RUSSIAN BANKING SUPERVISION AND REGULATION IN THE LIGHT OF BASEL II AND BASEL III IMPLEMENTATION IN THE RUSSIAN BANKING SYSTEM - K. R. Kakhrimanova (Модернизация, инновация, развитие, 2015)
The article focuses on the current situation in the Russian banking supervision and regulation and namely the process of its reforming in accordance withBaselprinciples. A special concern of the article is the features of Russian banking sector that are obstacles in full implementation of Basel II and Basel III inRussiatoday.